Kisah Ḥadīṡ al-Ifki dalam Al-Qur’an Perspektif Maqāṣid al-Qur’ān Ibn ‘Āsyūr - Ferry firdausi, Ferry firdausi; Putri Alfia Halida; Nurhayati (IAIN Madura, 2024)
Cases of fake news have occurred since ancient times, where this act was pioneered by the Devil who made up false information and deceived Prophet Adam so that he was expelled from heaven. From here, fake news continues to grow and has several times affected righteous people such as Juraij, Siti Maryam and Siti 'Āisyah. In this modern era, fake news seems to be public consumption and many members of the public play a role as the main actors and masterminds of this act. Departing from this phenomenon, the author wants to examine the fake news story that happened to Siti ‘Āisyah and was immortalized by Allah in QS. an-Nūr: 11-22. The focus of the study in this article is how the fake news story (ḥadīṡ al-ifki) happened to Siti ‘Āisyah and what maqāṡid is contained in it. Maqāṡid approach used is maqāṡid al-Qurān Ibn 'Āsyūr. The article concludes that the Qur'ānic maqāṣid contained in the hadīth of al-ifki is correcting beliefs and guiding to the right path, moral improvement, establishing religious rulings (in this context, the prohibition of making false news) both general and specific, and giving advice both in the form of warnings and good news.